Effects of feeding frequency of an elevated plane of milk replacer and calf age on behavior, and glucose and insulin kinetics in male Holstein calves. (13th November 2018) - MacPherson, J.; Meale, S. J.; Macmillan, K.; Haisan, J.; Bench, C. J.; Oba, M.; Steele, M. A.
Abstract : Optimizing feeding regimens in early life to maximize lifelong growth and production are essential in the dairy industry. This study investigated the effects of milk replacer (MR) feeding frequency and calf age on behavior, and glucose and insulin kinetics of pre- and post-weaned calves fed an elevated plane of MR. Ten male Holstein calves (42.2±1.8 kg BW) were blocked by BW and randomly assigned to two treatments offering 8 l MR/day (150 g/l) in two (2×; meal size 4 l) or four (4×; meal size 2 l) feedings via an automated calf feeder. Milk replacer was gradually stepped down by 1 l/day during week 8, with calves being weaned by week 9. Water and pelleted calf starter were offered ad libitum . Individual intake of MR and starter were recorded daily, and BW was recorded weekly. The number of visits to the MR feeder (rewarded and unrewarded), and behaviors such as lying, cross-sucking, non-nutritive sucking and occupancy time in the feeder were recorded for individual calves from weeks 4 to 10. Jugular catheters were placed on weeks 4, 7 and 10 to facilitate postprandial blood sampling and glucose tolerance tests. Statistical analysis was conducted using the PROC GLIMMIX procedure (SAS) for behavioral observations, and the MIXED procedure (SAS) with repeated measures for BW, intake, plasma glucose and plasma insulin data. Final BW, starter and MR intake did not differ between treatments. There were no differences in observed calf behaviors; with the exception that 2× calves visited the MR feeder more often ( P <0.01; total: unrewarded and rewarded). Baseline concentrations (mmol/l) and the maximum change in glucose (delta, mmol/l) were greater and lower ( P =0.02) in 4×compared to 2×calves, respectively. Postprandial insulin AUC240 tended ( P =0.09) to be greater in 2×calves, compared to 4×calves at week 7. Similarly, T max (min), AUC240 and delta values (µU/ml) were greater ( P ⩽0.05) in 2×calves, compared to 4×calves. No treatment ×age interactions were observed for glucose or insulin during the glucose tolerance tests. Therefore, we conclude that feeding an elevated plane of MR (8 l/day) at a lower frequency (2× v . 4×) increased feeder visits, but not other hunger-related behaviors, and while postprandial glucose and insulin parameters varied, insulin sensitivity remained stable in Holstein dairy calves up to 10 weeks of age in calves consuming similar levels of calf starter.